Exfoliated β-Ga2O3 nano-belt field-effect transistors for air-stable high power and high temperature electronics. Issue 23 (27th May 2016) - Kim, Janghyuk; Oh, Sooyeoun; Mastro, Michael A.; Kim, Jihyun
Abstract : Exfoliated β-Ga2 O3 nano-belt field-effect transistors for air-stable high power and high temperature electronics have been demonstrated. Abstract : This study demonstrated the exfoliation of a two-dimensional (2D) β-Ga2 O3 nano-belt and subsequent processing into a thin film transistor structure. This mechanical exfoliation and transfer method produces β-Ga2 O3 nano-belts with a pristine surface as well as a continuous defect-free interface with the SiO2 /Si substrate. This β-Ga2 O3 nano-belt based transistor displayed an on/off ratio that increased from approximately 10 4 to 10 7 over the operating temperature range of 20 °C to 250 °C. No electrical breakdown was observed in our measurements up to V DS = +40 V and V GS = −60 V between 25 °C and 250 °C. Additionally, the electrical characteristics were not degraded after a month-long storage in ambient air. The demonstration of high-temperature/high-voltage operation of quasi-2D β-Ga2 O3 nano-belts contrasts with traditional 2D materials such as transition metal dichalcogenides that intrinsically have limited temperature and power operational envelopes owing to their narrow bandgap. This work motivates the application of 2D β-Ga2 O3 to high power nano-electronic devices for harsh environments such as high temperature chemical sensors and photodetectors as well as the miniaturization of power circuits and cooling systems in nano-electronics.